Toxoplasmosis prevalence in Egyptian diabetic patients - Mahmoud H Hemida; Samir A Shahat; Ahmed M.S Bayoumy; Khairy A Mohamed; Shady M Hassan (Wolters Kluwer Medknow Publications, 2018)
Background Infection with Toxoplasma gondii is one of the most common parasitic infections in humans worldwide. Nearly one-third of individuals worldwide have been exposed to this parasite. Diabetes mellitus is an important factor that increases the susceptibility and risk of various infestations in the host. Objective This study aimed to shed light on and evaluate the seroprevalence of T. gondii infection in diabetic patients. Patients and methods T. gondii antibodies were tested serologically in 50 patients with diabetes mellitus and 50 apparently healthy individuals as controls using the enzyme-linked immunosorbent assay technique. Results The seropositivity for anti-Toxoplasma immunoglobulin (Ig)G antibodies in the study groups was 46% in diabetic patients (group I) and 24% in the control group (group II), with P value of 0.03 indicating a statistically significant difference between the two groups. Only one patient in the diabetic group (group I) was positive for anti-Toxoplasma IgM, with P value of 0.98, showing no statistically significant difference between the two groups. Conclusion The seropositivity for anti-Toxoplasma antibodies in diabetic patients was found to be higher than that in nondiabetic patients. Anti-Toxoplasma IgG antibodies 46 versus 24% (P=0.03).